On the formation of pure and Pt-doped iron silicides using ball milling - Desimoni, Judith (2001)
The sequence of phase formations for elemental powders of stoichiometric FeSi2 and Fe1-xPtxSi2 (0.03 ≤ x ≤ 0.50) mixtures prepared by mechanical alloying at room temperature in an Ar atmosphere in a horizontal mill is presented. Sample evolution was followed by means of Mössbauer spectroscopy and x-ray diffraction. After the milling, the results indicate the formation of different disordered iron silicides, depending on milling time. The kinetics of iron silicide formation was also studied; a diffusion-controlled process with decreasing nucleation rate was found. In the case of Pt-doped samples, the segregation of Pt silicides was observed even for the smallest concentration, and no noticeable incorporation of Pt into the β-FeSi2 lattice could be inferred. Samples were also subjected to annealing at 1123 K for 4 h to produce ordering in the structures.